Probe - Bonanno, Margaret Wander (Simon & Schuster Ltd., 1992)
Winds of change are sweeping the galaxy, the Romulan Praetor is dead, and with his passing the Empire he ruled is in chaos. Now, on a small planet in the heart of the Neutral Zone, representatives of the United Federation of Planets and the Empire have gathered to discuss an era of peace.
Keywords: Interplanetary voyages -- Space ships -- McCoy, Leonard (Fictitious character)